Relationship Between Exclusive Breastfeeding and Nutritional Status of Toddlers - Kaluku, Khartini (JURNAL IBU DAN ANAK, 2025)
Stunting is a chronic nutritional problem that affects children's growth and development. Exclusive breastfeeding for the first six months has been identified as a key intervention to prevent stunting. However, the practice of exclusive breastfeeding remains suboptimal, including in Ambon City. This study aimed to determine the relationship between exclusive breastfeeding and the nutritional status of stunted toddlers in Batu Merah Village, Ambon City, in 2024. The study used a descriptive quantitative design with a cross-sectional approach and total sampling involving 22 stunted toddlers. Data were collected through interviews and height-for-age measurements, and analyzed using the Chi-Square test. The results showed a significant relationship between exclusive breastfeeding and the nutritional status of stunted toddlers (p = 0.017). Toddlers who were not exclusively breastfed had a higher risk of severe stunting. Therefore, promotion and education on the importance of exclusive breastfeeding should be strengthened, particularly in areas with high stunting prevalence.